Organizational Citizenship Behaviour and Demographic Profiling: An Exploration Study Among Local Government Workforce in Terengganu, Malaysia - Mohamad Ibrahim, Dr. Rashidah; Md Fadzil, Dr. Ahmad Firdause; Abu Bakar @ Harun, Dr. Nor Mazlina; Wan Mohd Amin, Prof. Dr. Wan Abd Aziz (BOOK PUBLISHER INTERNATIONAL, 2020)
Start-ups are new businesses, which need a good amount of equity to finance investments. Crowdfunding is an alternative instrument to collect money. It does not need the intervention of a bank, but allows to obtain the funds directly from the public by network platforms. This article focuses on the possibility for a start-up to raise capital through crowdfunding. The argument is quite known on an international level, even if scholars often focus on specific problems or on particular moments of the life cycle of the start-up. On the contrary, the two arguments are really new in Italy. The Italian crowdfunding market is young – the main increase in the platforms number (+63%) is between 2013 and 2014 - and the national regulation which allows to finance startups by crowdfunding is even more recent (latest legal document in 2017). The novelty of the topic explains the added value of this article. To the best of our knowledge, no previous study focused on the Italian start-ups financed by crowdfunding. We analyze the phenomenon from the birth of the different platforms (2005 for the first one) since the end of the first semester 2018.